Indexing a bond's call price: an analysis of make-whole call provisions - Mann, Steven V.; Powers, Eric A. (Journal of Corporate Finance, 2003)
We analyze a new form of call provision known as a “make-whole” call, which utilizes a floating call price based on the level of current interest rates. As rates drop (rise), the call price increases (decreases.) Usually, a floor at par sets a minimum call price. This provision effectively eliminates the reinvestment rate risk associated with bonds with fixed-price call provisions. Survey results indicate a majority of Chief Financial Officers (CFOs) believe make-whole call provisions are “costless.” Analysis of 318 recent, make-whole call bonds indicates that this provision is indeed priced. On average, the at-issue yield-to-maturity of a make-whole call bond is 11.2 basis points higher than the yield of a comparable straight bond.